UNIA EUROPEJSKA W OBLICZU PANDEMII COVID-19 - Turczyński, Paweł (Polityka i Społeczeństwo, 2021)
The coronavirus pandemic that hit the world in early 2020 has weakened Europe very severely. In the first period (January-February), the disease was often neglected, which allowed it to spread rapidly. In March, panic struck European societies, the health systems of many countries collapsed, and governments introduced drastic restrictions on civil liberties and on the functioning of the economy. The European Union, which was helpless in the first period, took steps in the spring to restore the European economy after the end of the epidemic.